Analysis of Distance Learning Implementation Reviewed from Students Learning Interest of Culinary Program SMK Negeri 2 Depok - Muna, Asyya Rozana; Febriana, Rina; Sachriani, Sachriani (Universitas Negeri Padang, 2022)
This study aims to determine the distance learning system and the description of students' interest in learning while participating in distance learning at SMK Negeri 2 Depok during the COVID-19 pandemic. The location of this research is at SMK Negeri 2 Depok from October 2020 to August 2021. This research uses a qualitative descriptive method. Class X students of SMK Negeri 2 Depok are the population in this study. The results of interviews, questionnaires, and observations in the student class are the results of data analysis used. The instruments in this study were interview guidelines and questionnaire sheets. This research proves that distance learning at SMK Negeri 2 Depok is not going well. The analysis found from student responses showed various complaints, including quality indicators on aspects of distance learning, especially on the role of teachers and the learning platform used with the lowest average score, which is 2.621. Then from the aspect of learning interest, it shows that students do not have feelings of pleasure in participating in distance learning as indicated by the lowest average score, which is 1,747. Suggestions from this research is necessary to improve the quality of distance learning at SMK Negeri 2 Depok by providing distance learning training to teachers and being able to maximize the use of diverse learning platforms, so that students' interest in learning during the COVID-19 pandemic can increase while participating in distance learning.